The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1007/s10461-017-2011-3
|View full text |Cite
|
Sign up to set email alerts
|

The Use of Online Posts to Identify Barriers to and Facilitators of HIV Pre-exposure Prophylaxis (PrEP) Among Men Who Have Sex with Men: A Comparison to a Systematic Review of the Peer-Reviewed Literature

Abstract: Pre-exposure prophylaxis (PrEP) remains an under-utilized HIV prevention tool among men who have sex with men (MSM). To more comprehensively elucidate barriers and facilitators to PrEP use among US MSM, we conducted a systematic review of peer-reviewed published articles and content analysis of online posts about PrEP. We searched peer-reviewed databases (Medline, Web of Science, Google Scholar) using MESH headings and keywords about PrEP and/or HIV prevention from 2005 to 2015. We included original studies am… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
56
0
1

Year Published

2018
2018
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(65 citation statements)
references
References 44 publications
6
56
0
1
Order By: Relevance
“…Finally, the PrEP users who participated in our study identified an important role for peer support in initiating and continuing PrEP use and expressed significant enthusiasm for sharing their own experiences. This finding adds to previous research demonstrating that peer support or approval can facilitate PrEP uptake (Hannaford et al, 2018;Koechlin et al, 2017). While peer-to-peer or patient navigation interventions are recommended for promoting retention in HIV care, more research is needed to explore how similar interventions may be used to support PrEP use.…”
Section: Discussionsupporting
confidence: 51%
“…Finally, the PrEP users who participated in our study identified an important role for peer support in initiating and continuing PrEP use and expressed significant enthusiasm for sharing their own experiences. This finding adds to previous research demonstrating that peer support or approval can facilitate PrEP uptake (Hannaford et al, 2018;Koechlin et al, 2017). While peer-to-peer or patient navigation interventions are recommended for promoting retention in HIV care, more research is needed to explore how similar interventions may be used to support PrEP use.…”
Section: Discussionsupporting
confidence: 51%
“…Lack of interest or unwillingness to use PrEP appears to be associated with concerns about side effects (Goedel et al, 2016;Mutchler et al, 2015), lack of knowledge (Goedel et al, 2016), perceived inaccessibility and unaffordability (Calabrese et al, 2016;Goedel et al, 2016;Hubach et al, 2017;Kubicek et al, 2015;Oldenburg et al, 2016;Pérez-Figueroa et al, 2015;Whitfield, John, Rendina, Grov, & Parsons, 2018), perceived stigma (Franks et al, 2018;Hubach et al, 2017;Kubicek et al, 2015;Mutchler et al, 2015;Pérez-Figueroa et al, 2015;Young, Flowers, & McDaid, 2016), and 1 3 the perception that PrEP will lead to reduced condom use and greater sexual risk behavior (Eaton et al, 2017b;Grov, Rendina, Whitfield, Ventuneac, & Parsons, 2016;Hoff et al, 2015;Kubicek et al, 2015;Oldenburg et al, 2016;Pérez-Figueroa et al, 2015). Research has begun to document positive changes to sex and sexual culture some men on PrEP identify, such as more direct communication about HIV (Hannaford et al, 2018), reduced stigma against HIV-positive partners (Storholm, Volk, Marcus, Silverberg, & Satre, 2017), and reduced anxiety associated with sex (Brooks et al, 2012;Hojilla et al, 2016;Kwakwa et al, 2016;Storholm et al, 2017).…”
Section: Prep Public Health and Sexual Culturementioning
confidence: 99%
“…8,12,13 Research among potential PrEP users identifies awareness and knowledge of PrEP, costs, side effects, PrEP stigma, beliefs about HIV, and access to health care as important factors impacting uptake of PrEP. [14][15][16][17][18][19][20][21] Findings from open-label trials and demonstration projects have been similar, [22][23][24] although research in these contexts has focused on adherence and sexual behavior changes rather than uptake. [25][26][27][28][29][30] Others have studied provider barriers to PrEP implementation, finding that provider education is an important aspect of PrEP access.…”
Section: Introductionmentioning
confidence: 98%